DEVELOPMENT OF ORALLY DISINTEGRATING FIXED DOSE COMBINATION TABLETS CONTAINING ONDANSETRON HYDROCHLORIDE AND DEXKETOPROFEN TROMETAMOL - (:unkn) unknown (POLSKIE TOWARZYSTWO FARMACEUTYCZNE, 2017)
Orally disintegrating tablet formulations that involve active pharmaceutical ingredients in combination with a non-steroidal anti-inflamatory (dexketoprofen trometamol) and 5-HT 3 receptor antagonist (ondansetron hydrochloride) to prevent pain and nausea/vomiting during cancer therapy have been developed; in vitro dissolution profiles of these formulations have been examined and evaluated. 9 different formulations were generated to observe the effect of disintegrants that have various mechanisms of action, and the effect of lubricants on dissolution profiles in several media. Direct compression and wet granulation manufacturing methods were used throughout the trials of 9 formulations. Dissolution tests were conducted for both active pharmaceutical ingredients in pH 1.2 HCl acid, pH 4.5 acetate and pH 6.8 phosphate buffers for 9 formulations. then an optimized formulation was defined. Dissolution profiles of the optimized formulation were compared with two different reference products. Selected formulations, reference products and the optimized formulation were stored in accelerated stability conditions. Then, the alteration of tablets was evaluated. To our knowledge in this study, it was the first time that dexketoprofen trometamol and ondansetron hydrochloride were combined as an orally disintegrating fixed dose combination.
Keywords: dexketoprofen; ondansetron; ODT; pain; nausea; POSTOPERATIVE PAIN; DISSOLUTION RATE; IN-VITRO